Effects of an Exercise Intervention on Bone Mass in Pediatric Bone Tumor Patients - Müller, C.; Winter, C.; Boos, J.; Gosheger, G.; Hardes, J.; Vieth, V.; Rosenbaum, D. (International Journal of Sports Medicine, 2014)
The aim was to evaluate the effects of additional exercises during inpatient stays on bone mass in pediatric bone tumor patients. 21 patients were non-randomly allocated either to the exercise group (n=10) or the control group (n=11). DXA of the lumbar spine, the non-affected femur and both calcanei was performed after completion of neoadjuvant chemotherapy (baseline), as well as 6 and 12 months after baseline. Bone mineral content (BMC), bone mineral density (BMD) and height-corrected lumbar spine Z-scores were determined. Group changes after 6 and 12 months were compared by covariance analyses. Additionally, daily physical activities (PA) were assessed by means of accelerometry. After adjusting for initial age, height and weight, mean reductions in lumbar spine and femoral BMC were lower in the exercise group (not significant). Effect sizes during the observational period for lumbar spine and femur BMC were generally small (partial η²=0.03). The exercise group demonstrated substantially higher PA levels in terms of gait cycles per day, per hour and moderate PA (activities above 40 gait cycles per minute). Additional exercises for bone tumor patients are feasible during hospitalization. Though the intervention did not influence BMC, it appeared beneficial regarding PA promotion with respect to volume and intensity.
Keywords: bone mass; training program; physical activity; sarcoma; children; adolescents